Plasmodium falciparum antioxidant protein as a model enzyme for a special class of glutaredoxin/glutathione-dependent peroxiredoxins - Djuika, Carine F.; Fiedler, Sabine; Schnölzer, Martina; Sanchez, Cecilia P.; Lanzer, Michael; Deponte, Marcel (Biochimica et biophysica acta. General subjects, 2013)
Background - Peroxiredoxins are important heterogeneous thiol-dependent hydroperoxidases with a variety of isoforms and enzymatic mechanisms. A special subclass of glutaredoxin/glutathione-dependent peroxiredoxins has been discovered in bacteria and eukaryotes during the last decade, but the exact enzymatic mechanisms of these enzymes remain to be unraveled. - Methods - We performed a comprehensive analysis of the enzyme kinetics and redox states of one of these glutaredoxin/glutathione-dependent peroxiredoxins, the antioxidant protein from the malaria parasite Plasmodium falciparum, using steady-state kinetic measurements, site-directed mutagenesis, redox mobility shift assays, gel filtration, and mass spectrometry. - Results - P. falciparum antioxidant protein requires not only glutaredoxin but also glutathione as a true substrate for the reduction of hydroperoxides. One peroxiredoxin cysteine residue and one glutaredoxin cysteine residue are sufficient for catalysis, however, additional cysteine residues of both proteins result in alternative redox states and conformations in vitro with implications for redox regulation. Our data furthermore point to a glutathione-dependent peroxiredoxin activation and a negative subunit cooperativity. - Conclusions - The investigated glutaredoxin/glutathione/peroxiredoxin system provides numerous new insights into the mechanism and redox regulation of peroxiredoxins. - General significance - As a member of the special subclass of glutaredoxin/glutathione-dependent peroxiredoxins, the P. falciparum antioxidant protein could become a reference protein for peroxiredoxin catalysis and regulation.